KONSEP SANKSI PIDANA PENJARA CICILAN SEBAGAI ALTERNATIF PEMENJARAAN BARU DALAM UPAYA MENGATASI OVER CAPACITY/KELEBIHAN KAPASITAS DI DALAM LEMBAGA PERMASYARAKATAN - Muhammad Fauzar Rivaldy; Mety Rahmawati (Fakultas Hukum Universitas Tarumanagara, 2018)
Law is a rule that applies to every country which has been arranged expressly and applied to society governing all actions from every society and in essence the law is nothing but protection of human interest, in the form of rule or norm. Criminal law is a rule that regulates the act that should not be done, which if violated will be subject to criminal sanctions imprisonment. Prisons are a place to give treatment to the offenders. But at this time the prison is not able to provide the maximum treatment, and prisons today have many problems that occur, namely one of over-capacity. The government has not been able to provide solutions to the problems that occur in prisons, but the current legal reform, especially the criminal law is expected to overcome the problems that occur in the prison, so as to reduce the over-capacity that occurs in prison. In the RKUHP there is one article that regulates the imposition of criminal in a different way that is imprisonment executed by way of installment, Alternative to imprisonment which is expected to reduce the over-capacity that occurs in prison.